Promising nanotherapeutics of stem cell extracellular vesicles in liver regeneration - Na Guo; Yan Wang; Zhaofeng Wen; Xiaofei Fan (Regenerative Therapy)
Extracellular vesicles (EVs) have gainedsignificant attention due totheir crucialroles invarious biological systems. This review aims to explore the functions of EVs in both in physiological and pathological states of the liver, with a specific focus on the potential mechanisms and concrete evidence of EVs in liver regeneration processes. The review begins by emphasizing the importance of EVs in maintaining liver health and their involvement in different pathological conditions, starting from the liver's own EVs. Reviewing the role of EVs in liver diseases to reveal the impact of EVs in pathological processes (e.g., hepatitis, liver fibrosis, and cirrhosis) and elucidate their signaling functions at the molecular level. Subsequently, the work concentrates on the functions of EVs in liver regeneration, revealing their key role in repair and regeneration following liver injury by carrying growth factors, nucleic acids, and other bioactive molecules. This part not only theoretically clarifies the mechanisms of EVs in liver regeneration but also experimentally demonstrates their role in promoting liver cell proliferation, inhibiting apoptosis, regulating immune responses, and fostering angiogenesis, laying the groundwork for future clinical applications. Moreover, this work provides a comprehensive analysis of the challenges faced by existing EV-based therapies in liver regeneration and offers prospects for future research directions. It highlights that despite the tremendous potential of EVs in treating liver diseases, there are still technical challenges (e.g., EV isolation and purification, dosage control, and targeted delivery). To overcome these challenges, the review suggests improvements to current technologies and the development of new methods to realize the clinical application of EVs in treating liver diseases.